The Effectiveness of Reciprocal Teaching Learning Model on Reading Comprehension Skill of Grade VIII Student at SMPN 4 Sungai Kerjan - Muhammad Habibi; Diana Oktavia; Ridho Kurniawan (Master Journal of Future Education, 2025)
Reading comprehension is essential to learning English; however, many students still struggle to master it. To overcome this issue, the reciprocal teaching model was applied as a solution, emphasizing the strategies of predicting, questioning, clarifying, and summarizing, with the expectation of enhancing students' engagement and reading comprehension skills. This study employed an experimental design using a Pre-test and Post-test Nonequivalent Control Group Design. The subjects consisted of class VIII.7 with 32 students as the experimental group and class VIII.6 with 30 students as the control group. Data were collected through pre-tests and post-tests in essay form and analyzed to examine effectiveness using an independent t-test and Normalized Gain Score (N-Gain). The results of the independent t-test showed a significant difference between the two groups, both in the pre-test (Sig. 0.002 < 0.05) and post-test (Sig. 0.004 < 0.05). The N-Gain analysis supported these findings, as the experimental class obtained an average N-Gain of 0.6325 (medium to high category) with 72% mastery. In comparison, the control class only achieved an average N-Gain of 0.3039 (low to medium category) with 27% mastery. Thus, it can be concluded that reciprocal teaching effectively improves students' reading comprehension skills